Legal Protection for The Parties Shopee Paylater Service Users - Sania Puspita Anggraini; Hardian Iskandar; Dodi Jaya Wardana (Syiar Hukum, 2022)
With the development of technology in the payment system, electronic money has various forms: Paylater. Paylater is now in great demand by the public because it can make it easier for them to make transactions and complete payments later. In addition, the interest provided is quite affordable. This study aims to find out and explain the form of legal standing, legal protection, and legal consequences for Shopeepaylater users. The study results found that the parties' legal position in Shopeepaylater is that the user acts as the recipient of the loan, and the Shopee acts as the lender. Legal protection in shopeepaylater uses repressive or settlement protection methods generally. This protection is in fines, imprisonment, and other additional penalties. The legal consequences when performing a Default following the agreed agreement that the Shopeepaylater service user will have their Shopeepaylater limit reduced, record late payments in the OJK SLIK (Financial Information Service System of the Financial Services Authority), etc.